Fiscal Policies and Rules in the Face of Revenue Volatility within Southern Africa Customs Union Countries (SACU) - Basdevant, Olivier (IMF Working Papers; Working Paper ;, 2012)
Following the onset of the global economic crisis in 2008, SACU member countries have witnessed a significant growth slowdown, and a deterioration of their fiscal balances. This paper (i) assesses options for the design of the needed fiscal consolidation, and (ii) discussed medium-term fiscal policy rules that would help maintain a sound fiscal stance once consolidation has taken place. The main messages are: (i) government consumption cuts appears to minimize the negative impact on growth, and would be appropriate given the relatively large size of the public sector in each country, (ii) fiscal rules could be of particular interest for SACU members notably, a new customs revenue-sharing formula, procedural rules to strengthen budget process, and numerical rules at the national level.